2016
DOI: 10.1016/j.intimp.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Lectin from Abelmoschus esculentus reduces zymosan-induced temporomandibular joint inflammatory hypernociception in rats via heme oxygenase-1 pathway integrity and tnf-α and il-1β suppression

Abstract: Temporomandibular joint (TMJ) disorders show inflammatory components, heavily impacting on quality of life. Abelmoschus esculentus is largely cultivated in Northeastern Brazil for medicinal purposes, having it shown anti-inflammatory activity. We evaluated A. esculentus lectin (AEL) efficacy in reducing zymosan-induced temporomandibular joint inflammatory hypernociception in rats along with the mechanism of action through which it exerts anti-inflammatory activity. Animals were pre-treated with AEL (0.01, 0.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Here, we showed that S. maritima (5 mg/kg) significantly increased IL-10 gingival levels, an anti-inflammatory cytokine, while decreasing the pro-inflammatory cytokines TNF-α and CINC-1. Alternative therapeutic approaches based that inhibit TNF-α production have been successfully used for the pre-clinical and clinical treatment of chronic inflammatory diseases, particularly rheumatoid arthritis and temporomandibular joint disorders (Feldmann, 2002 ; Araújo et al, 2013 ; Freitas et al, 2016 ; Alves et al, 2017 ). Further, when mRNA expression for TNF-α, IL-1β, iNOS, and RANK were evaluated, S. maritima 5 mg/kg significantly reduced mRNA expression for all these genes compared to the vehicle group.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we showed that S. maritima (5 mg/kg) significantly increased IL-10 gingival levels, an anti-inflammatory cytokine, while decreasing the pro-inflammatory cytokines TNF-α and CINC-1. Alternative therapeutic approaches based that inhibit TNF-α production have been successfully used for the pre-clinical and clinical treatment of chronic inflammatory diseases, particularly rheumatoid arthritis and temporomandibular joint disorders (Feldmann, 2002 ; Araújo et al, 2013 ; Freitas et al, 2016 ; Alves et al, 2017 ). Further, when mRNA expression for TNF-α, IL-1β, iNOS, and RANK were evaluated, S. maritima 5 mg/kg significantly reduced mRNA expression for all these genes compared to the vehicle group.…”
Section: Discussionmentioning
confidence: 99%
“…The extract of AE could attenuate vascular impairment and reduce the levels of inflammatory factors in load-induced fatigued rats [18,49]. Here we suppose that AE and Metformin may improve high fat induced endothelial inflammation by regulating miR-146a and miR-155.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, AE was reported to improve islet structure in diabetes by PPAR-dependent mechanism [54], and active subfractions of AE substantially attenuated free fatty acid-induced β cell apoptosis through inhibiting dipeptidyl peptidase-4 [55]. Despite glucose and lipid metabolism, Huangkui and lectin, the extracts of AE, were found to inhibit inflammation response in kidney and temporomandibular joint [49,56]. Additionally, quercetin-3-O-gentiobiose, the extract of AE, had anti-fatigue and vasoprotective effects through enhancing the activities of antioxidant enzymes and improving the levels of inflammatory cytokines, thus attenuating vascular endothelial dysfunction induced by endurance swimming [18].…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with our previous report, indicating that PSPs‐EH80 is more effective than PSPs in reducing the oxidative stress‐induced cell damage in HaCaT cells . Some recent studies pointed out that the Abelmoschus esculentus lectin (AEL) possessed an anti‐inflammatory activity via promoting HO‐1 overexpression and decreasing TNF‐α and IL‐1β expression …”
Section: Discussionmentioning
confidence: 99%